2009
DOI: 10.1254/jphs.09077fp
|View full text |Cite
|
Sign up to set email alerts
|

Synephrine, a Component of Evodiae Fructus, Constricts Isolated Rat Aorta via Adrenergic and Serotonergic Receptors

Abstract: Abstract. We investigated the effects of Evodiae Fructus and synephrine, one of the components of Evodiae Fructus, on blood vessels. We found that Evodiae Fructus (1 × 10 −6 -3 × 10 −4 g/mL) had constrictive effects on rat aorta. The vasoconstrictive effects of Evodiae Fructus were significantly inhibited by pretreatment with prazosin (adrenergic α 1 -receptor antagonist), BRL15572 [5-hydroxytryptamine (5-HT) 1D antagonist], and ketanserin (5-HT 2A antagonist), but its vasoconstrictive effects were not inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
(14 reference statements)
2
27
0
Order By: Relevance
“…Hibino et al () assessed the ability of p ‐synephrine to constrict isolated rat aorta at concentrations of 1 × 10 ‐7 to 3 × 10 ‐5 mol/L. Using selected receptor antagonists, the authors concluded that the constrictor effects were exerted via α‐1adrenoreceptors and serotonergic (5‐HT 1D and 5‐HT 2A ) receptors.…”
Section: Mechanism and Receptor Bindingmentioning
confidence: 99%
“…Hibino et al () assessed the ability of p ‐synephrine to constrict isolated rat aorta at concentrations of 1 × 10 ‐7 to 3 × 10 ‐5 mol/L. Using selected receptor antagonists, the authors concluded that the constrictor effects were exerted via α‐1adrenoreceptors and serotonergic (5‐HT 1D and 5‐HT 2A ) receptors.…”
Section: Mechanism and Receptor Bindingmentioning
confidence: 99%
“…Based on receptor binding studies using human and animal cells, m -synephrine exerts its effects on α -  , β -1 and β -2 adrenergic receptors [2832] resulting in increased blood pressure and heart rate effects. Jordan et al [28] compared the receptor binding activities of m - and p -synephrine and m - and p -octopamine (N-demethyl p -synephrine; Figure 8) with norepinephrine in guinea pig atria and trachea [28].…”
Section: Receptor Binding Studiesmentioning
confidence: 99%
“…Hibino et al [32] examined the ability of p -synephrine to constrict isolated rat aorta at concentrations of 1 × 10 −7 to 3 × 10 −5  M. Using selected receptor antagonists, the authors concluded that the constrictor effects were exerted via α -1 adrenoreceptors and serotonergic (5-HT 1D and 5-HT 2A ) receptors. Again, the concentrations of p -synephrine used to produce aortic constriction were significantly higher than the peak blood levels (2 ng/mL) observed when 46.9 mg p -synephrine was given orally to human subjects and exerted little or no effect on heart rate or blood pressures [33].…”
Section: Receptor Binding Studiesmentioning
confidence: 99%
“…[1-14 C]oleic acid (56 mCi/mmol) and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]octanoic acid (50 mCi/mmol).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown, for example, that p-synephrine binds to serotoninergic receptors [4]. Likewise, an action of p-synephrine via adrenergic receptors has been documented [5] [6] [7]. Acute oral administration of elevated doses of a C. aurantium extract or psynephrine produced reversible toxic effects, probably due to unspecific adrenergic stimulation [3].…”
Section: Introductionmentioning
confidence: 99%